Islamic Religious Education Teacher Strategies in Implementing Differentiated Instruction to Enhance Student Learning Motivation - Muslim, Imam; Nasarudin, Nasaruddin; Kaharuddin, Kaharuddin (IAIN KENDARI, 2025)
This study aims to analyze the strategies implemented by Islamic Religious Education teachers in differentiation learning to improve students' learning motivation at SMAN 3 Kota Bima. The main problem studied is how the implementation of differentiation learning can affect students' learning motivation and what factors support and inhibit the implementation of the strategy. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. Data were analyzed using descriptive analysis techniques. The results of the study indicate that differentiation learning implemented by Islamic Religious Education teachers is able to improve students' learning motivation, especially with an approach that focuses on the needs and learning styles of different students. The main supporting factors include teacher competence, facility support, and parental participation. However, there are also inhibiting factors such as limited teacher understanding and inadequate facilities. This study provides an important picture of how differentiation learning can be optimized to improve students' learning motivation.